2011
DOI: 10.3109/10903127.2011.561401
|View full text |Cite
|
Sign up to set email alerts
|

Role of Emergency Medical Services in Disaster Response: Resource Document for the National Association of EMS Physicians Position Statement

Abstract: The National Association of EMS Physicians (NAEMSP) advocates for a strong emergency medical services (EMS) role in all phases of disaster management-preparedness, response, and recovery. Emergency medical services administrators and medical directors should play a leadership role in preparedness activities such as training and education, development of performance metrics, establishment of memoranda of understanding (MOUs), and planning for licensure and liability issues. During both the planning and response… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
59
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(60 citation statements)
references
References 44 publications
1
59
0
Order By: Relevance
“…These findings were comparable to previous reports from different studies (Fernandez et An education and training score indicated that 67% of the surveyed EMTs had a high level of education and training, 20% a moderate level and 12% a poor level (Table 3). These findings support previous reports that indicated gaps in education and training regarding MCIs medical management in EMS professionals (Fischer et al, 2008;Catlett et al, 2011).…”
Section: Discussionsupporting
confidence: 91%
“…These findings were comparable to previous reports from different studies (Fernandez et An education and training score indicated that 67% of the surveyed EMTs had a high level of education and training, 20% a moderate level and 12% a poor level (Table 3). These findings support previous reports that indicated gaps in education and training regarding MCIs medical management in EMS professionals (Fischer et al, 2008;Catlett et al, 2011).…”
Section: Discussionsupporting
confidence: 91%
“…EMS systems need to be efficient when it comes to plan for, respond to, and recover from natural disasters or disease outbreaks. It is unthinkable what the consequences would be if EMS providers did not commit with their social and ethical responsibilities to do what is expected of them during crisis [29]. Research studies show that healthcare workers are generally -except for nuclear events-least willing to work during epidemics [30].…”
Section: Discussionmentioning
confidence: 99%
“…In this regard, appropriate response and short time intervals (response time, scene time and evacuation time) together with adequate care are the most important aims for EMS (7-10). These systems are also the backbone of disaster response and should build such preparedness on their daily activities (11, 12). The impact of time intervals has been discussed in many studies, published during last decades (13-16).…”
Section: Introductionmentioning
confidence: 99%